Estrus synchronization with Cloprostenol and effect off ollitropin treatment on superovulatory response and embryo recovery in Sahiwal Cows - MISHRA, O P; KHAN, J R; AWASTHl, M K (The Indian Journal of Animal Reproduction, 2002)
Estrus was synchronized in 18 donors and 28 recipient cows with two injection of 500μgm cloprostenol 11days apart. Follitropin was administered in three different doses viz 400 mg NIH, 300mg NIH and 200mg NIH todonors(n=l 8) which were randomly and equally divided in three groups,A.B and C. Significantly (p
Keywords: Sahiwal cows; follitropin; embryo; super ovulation